2013
DOI: 10.1002/hep.26305
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a suppresses tumor growth and metastasis of human hepatocellular carcinoma by targeting interleukin-6-Stat3 pathway

Abstract: Down-regulation of microRNA-26a (miR-26a) is associated with poor prognosis of hepatocellular carcinoma (HCC), but its functional mechanism in HCC remains unclear. In this study, we investigated the roles of miR-26a in tumor growth and metastasis of HCC and found that miR-26a was frequently down-regulated in HCC tissues. Down-regulation of miR-26a correlated with HCC recurrence and metastasis. Through gain-and loss-offunction studies, miR-26a was demonstrated to significantly inhibit in vitro cell proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
183
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(208 citation statements)
references
References 41 publications
22
183
0
3
Order By: Relevance
“…[32][33][34][35] In addition, clinical studies showed that patients with higher level of miR26a in tumor tissues have better prognosis, possibly through the role of miR-26a in inhibition of cell proliferation via targeting cyclin D2, cyclin E2, and IL-6. 36,37 Our results suggest that miR-26a acts through arresting G1-S transition to suppress A549 cell proliferation, and this effect is mediated by HMGA2-E2F1-Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 76%
“…[32][33][34][35] In addition, clinical studies showed that patients with higher level of miR26a in tumor tissues have better prognosis, possibly through the role of miR-26a in inhibition of cell proliferation via targeting cyclin D2, cyclin E2, and IL-6. 36,37 Our results suggest that miR-26a acts through arresting G1-S transition to suppress A549 cell proliferation, and this effect is mediated by HMGA2-E2F1-Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 76%
“…MiR26 has been shown to function as a tumor suppressor miRNA by targeting multiple genes, including EZH2 in nasopharyngeal carcinoma (35), Burkitt lymphoma (36), and lung cancer (37), IL6 in hepatocellular carcinoma (38), and CKS2 in papillary thyroid carcinoma (39). In this study, we show that miR26a and miR26b also function as tumor suppressor miRNAs in lung cancer, as miR26a and miR26b were significantly downregulated in lung cancer specimens compared with the paired normal tissues and miR26a and miR26b mimics inhibited the proliferation, migration, and invasion of lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 transcript is positively regulated by Arid 5a (Masuda et al 2013), TNFα and IL-1β (Gruys et al 2005), and negatively regulated by regnase-I (Iwasaki et al 2011), bromodomain-containing protein 4 (BRD4) (Barrett et al 2014), and microRNAs (miRs) e.g. miR-26a (Yang et al 2013), miR-142 (Sun et al 2013), miR-146a (He et al 2014), miR-146b (Xiang et al 2014), miR-187 (Rossato et al 2012), miR-200s (Dou et al 2013) and miR-329 (Garg et al 2013) (Fig. 1).…”
Section: Biology and Functions Of Il-6mentioning
confidence: 99%